Financial Development and Sustainable Exports: Evidence from Firm-Product Data - Melise Jaud; Madina Kukenova; Martin Strieborny (Lund University, School of Economics and Management, Department of Economics, 2013)
We combine a novel measure of export-related financial needs at the product level with a unique database of firm-product export data from five developing countries. Using the tools of survival analysis and controlling for firm and products fixed effects, we then examine the impact of financial development on the long-term trade. Finance matters for sustainable export performance, as goods with higher export-related financial needs disproportionately benefit from better financial development. Our results complement existing literature on finance and trade, which has relied on production-based measures of financial dependence at the industry or firm level.
Keywords: F10; G10; O16; 330; fi…nance and trade; export survival; agri-food trade; SPS regulation